2014
DOI: 10.1002/chir.22339
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Degradation of (2RS,3RS)‐Paclobutrazol in Peach and Mandarin Under Field Conditions

Abstract: In this study we investigated the enantioselective degradation of (2RS,3RS)-paclobutrazol in peach and mandarin fruits under field conditions after foliar treatment at 500 mg active ingredient/L using a Lux Cellulose-1 chiral column on a reverse-phase liquid chromatography-tandem mass spectrometry system. Degradations of paclobutrazol in both fruits followed first-order kinetics, with half-lives of about 9 days. Initial deposits were 1.63 mg/kg on peach and 1.99 mg/kg on mandarin; terminal concentrations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…The enantiomeric fractions (EF) were defined as E(+)/(E(+)+E(–)) for enantiomers with a known elution order, where E(+), E(–) are peak areas of respective enantiomers with their signs of optical rotation. The order of elution of paclobutrazol enantiomers was confirmed to be (+)(2 R , 3 R )‐paclobutrazol and (–)(2 S , 3 S )‐paclobutrazol based on published data . Therefore, in this article the EF of paclobutrazol was calculated from the equation EF = [2 R , 3 R ] / ([2 R , 3 R ] + [2 S , 3 S ]) and is graphed in Figure B.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…The enantiomeric fractions (EF) were defined as E(+)/(E(+)+E(–)) for enantiomers with a known elution order, where E(+), E(–) are peak areas of respective enantiomers with their signs of optical rotation. The order of elution of paclobutrazol enantiomers was confirmed to be (+)(2 R , 3 R )‐paclobutrazol and (–)(2 S , 3 S )‐paclobutrazol based on published data . Therefore, in this article the EF of paclobutrazol was calculated from the equation EF = [2 R , 3 R ] / ([2 R , 3 R ] + [2 S , 3 S ]) and is graphed in Figure B.…”
Section: Resultsmentioning
confidence: 72%
“…This study also indicated the enzymatic stereoselective behavior of paclobutrazol enantiomers in organisms and other environmental matrices. 8,13,17 As a consequence, our investigation may provide reference data for the safe and efficient use of the chiral plant growth regulator paclobutrazol.…”
Section: Kinetic Degradation In Rat Liver Microsomesmentioning
confidence: 91%
See 1 more Smart Citation
“…The reasons for this might be the use of yeast as a starter. In addition, compared with A0d, the relative abundance of Aureobasidium in AN7d and AP7d was significantly lower ( P <.05, Q < 0.05), indicated that the fermentation system of wine was not suitable for the growth of Aureobasidium , and previous study illustrated that Aureobasidium is an important saprophytic yeast, and usually found in various habitats . In the fermentation system with no yeast added, Schwanniomyces and Cladosporium were the dominant fungi at the beginning of fermentation (B0d), and after 7 days of fermentation, the abundance of Pichia was increased and became the main fungi (BN7d and BP7d).…”
Section: Resultsmentioning
confidence: 99%
“…(2R, 3R)-Paclobutrazol was preferentially degraded in mandarin but enriched in peach. 18 Fermentation food is a traditional food worldwide through thousands of years under the action of microorganisms. 19,20 Different foods have been fermented in daily life such as vegetable, bean, fruit, dairy, and fish.…”
Section: Introductionmentioning
confidence: 99%